Enterosalpingeal fistula complicating Crohn's disease: Report of two cases and review of the literature. (September 2021) - Haddad, A.; Sebai, A.; Maghrebi, H.; Chaker, Y.; Jouini, M.; Kacem, M.
Abstract: Introduction and importance: Reports of enterosalpingeal fistulae complicating Crohn's disease are scarce. They involve the last ileal loop and lead to a progressive destruction of the salpinx. Usually, no genital symptoms are found. In all the cases reported in the literature, the fistula was diagnosed intra-operatively and resection of the right salpinx was performed without the patient's pre-operative consent. Case presentation: We describe 2 cases of women presenting with an Enterosalpingeal fistulae complicating Crohn's disease. Radiological findings allowed a pre-operative diagnosis. Thus, the patients were warned of the right salpinx resection and consent was obtained. Clinical discussion: Enterosalpingeal fistulae complicating Crohn's disease are exceptional. Indeed, to the best of our knowledge, only five cases have been reported till now. In all the reported cases, no genital signs were present. As for our patients who didn't experience such symptoms. Moreover, no radiological evidence of the enterosalpingeal fistula was found in the literature. Consequently, the fistula was always diagnosed intra-operatively. For our patients, radiological findings allowed a pre-operative diagnosis. This permitted to warn them of a possible resection of the fallopian tube. Intra-operative findings were unfortunately conflicting with its preservation. Conclusion: Enterosalpingeal fistula is an exceptional complication of the Crohn's disease. No clinical findings are present. The diagnosis should be evoked when the CT-scan or the MRI show an abnormal apposition between the fallopian tube, the last loop and the cecum. Surgical resection of the involved salpinx with the diseased intestinal segment is unfortunately usually needed in a young patient population. Highlights: Report of two cases of an unusual form of Crohn's disease. Unique preoperative imaging. Preoperative diagnosis of the fistulae. Thus, patients were warned of salpingectomy.